Rapid inhibition of interleukin-6 signaling and Stat3 activation mediated by mitogen-activated protein kinases - Sengupta, Tapas K. (The National Academy of Sciences, 1998)
Gene activation and cellular differentiation induced by interleukin-6 (IL-6) and transcription factor Stat3 are suppressed by several factors, including ionomycin, granulocyte/macrophage-colony-stimulating factor, and phorbol 12-myristate 13-acetate (PMA), that block IL-6-induced Stat3 activation. These inhibitory agents activate mitogen activated protein kinases (MAPKs), and thus the role of MAPKs in the mechanism of inhibition of Stat3 activation was investigated. Inhibition of IL-6-induced Stat3 activation by PMA and ionomycin was rapid (within 5 min) and did not require new RNA or protein synthesis. Inhibition of Stat3 DNA-binding activity and tyrosine phosphorylation by PMA, ionomycin, and granulocyte/macrophage-colony-stimulating factor was reversed when activation of the extracellular signal-regulated kinase (ERK) group of MAPKs was blocked by using specific kinase inhibitors. Expression of constitutively active MEK1, the kinase that activates ERKs, or overexpression of ERK2, but not JNK1, inhibited Stat3 activation. Inhibition of Stat3 correlated with suppression of IL-6-induction of a signal transducer and activator of transcription (STAT)-dependent reporter gene. In contrast to IL-6, activation of Stat3 by interferon-α was not inhibited. MEKs and ERKs inhibited IL-6 activation of Stat3 harboring a mutation at serine-727, the major site for serine phosphorylation, similar to inhibition of wild-type Stat3, and inhibited Janus kinases Jak1 and Jak2 upstream of Stat3 in the Jak-STAT-signaling pathway. These results demonstrate an ERK-mediated mechanism for inhibiting IL-6-induced Jak-STAT signaling that is rapid and inducible, and thus differs from previously described mechanisms for downmodulation of the Jak-STAT pathway. This inhibitory pathway provides a molecular mechanism for the antagonism of Stat3-mediated IL-6 activity by factors that activate ERKs.